First Described Case of Anterior and Posterior Segment Crystals in Phacolytic Glaucoma. Issue 5 (May 2017) - Peracha-Riyaz, Manal H.; Peracha, Zuhair H.; Spaulding, Justin; Baciu, Paul; Ahmed, Shareef; Imami, Nauman R.; Darnley-Fisch, Deborah; Desai, Uday
Abstract : Phacolytic glaucoma is an open-angle glaucoma that occurs when lens proteins from hypermature cataracts seep through an intact anterior capsule and induce obstruction of the trabecular meshwork by inflammatory cells. We review the case of a 66-year-old man who presented with acute pain, a hypermature cataract, prominent anterior chamber crystals, and elevated intraocular pressure. After cataract surgery was performed, iridescent crystals were noted in the posterior chamber. Anterior chamber crystals have been associated with phacolytic glaucoma, but this is the first case demonstrating crystals in the posterior chamber as well. Abstract : Supplemental Digital Content is available in the text.